Notices épigraphiques et onomastiques (Dacie romaine) (I) - Dana, Dan (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
This paper republishes 12 Greek and Latin inscriptions from Roman Dacia, in most cases with illustrations. Previous readings are improved and more ghost-names are removed. These inscribed monuments and objects (some of them, in the category of instrumentum inscriptum) are explained in their series or contexts, pertaining to the military milieu or the cosmopolitan side of the province.